2015
DOI: 10.1007/s13187-015-0960-7
|View full text |Cite
|
Sign up to set email alerts
|

Level of Awareness of Various Aspects of Lung Cancer Among College Teachers in India: Impact of Cancer Awareness Programmes in Prevention and Early Detection

Abstract: Lung cancer is one of the most common causes of cancer mortality among men in India and incidence is increasing, but actually, they are largely preventable diseases. In India, advanced stage at the time of presentation is responsible for high mortality and morbidity and early detection is the only way to reduce it. The purpose of this study is to know the level of awareness of various aspects of lung cancer among college teachers and impact of awareness programmes in its prevention and early detection. This as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The total sample size from primary studies was 3563 participants. Six studies showed majority of the participants to be males (19,(36)(37)(38)(39)(40) , two studies had a slight female preponderance (41,42), while one study (20) was a literature review . Of the nine studies included, 6 were cross-sectional studies (36-39, 41, 42), one was a pre-test and post-test study design (40), one was a prospective study (19) and one was a literature review (20).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The total sample size from primary studies was 3563 participants. Six studies showed majority of the participants to be males (19,(36)(37)(38)(39)(40) , two studies had a slight female preponderance (41,42), while one study (20) was a literature review . Of the nine studies included, 6 were cross-sectional studies (36-39, 41, 42), one was a pre-test and post-test study design (40), one was a prospective study (19) and one was a literature review (20).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Six studies showed majority of the participants to be males (19,(36)(37)(38)(39)(40) , two studies had a slight female preponderance (41,42), while one study (20) was a literature review . Of the nine studies included, 6 were cross-sectional studies (36-39, 41, 42), one was a pre-test and post-test study design (40), one was a prospective study (19) and one was a literature review (20). Of the nine included studies, eight studies described at least one lung cancer warning signs and symptoms (19,(36)(37)(38)(39)(40)(41)(42), while one study described the effectiveness of palliative care for lung cancer (20).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations